Analyzing Students’ Ability InWriting Giving Warnings Dialogues At Senior High School - siska Geby Monica; Nuzulul Isna (Institut Agama Islam Negeri Palopo, 2024)
This research aims to determine abilities and find out what causes students' mistakes in writing warning dialogues at Man 1 Aceh Barat Daya. This research was designed as a quantitative descriptive method Because this research describes variables that are supported by data in the form of numbers generated from the actual situation by using the method of observing students' scores in writing warning sentences, a method used to observe actual symptoms, events, or conditions in the field related to numbers or values. This research was designed systematically to be reliable, therefore, the steps in this research began with planning, introduction, compiling instruments, processing data, and concluding. In this research, it can be seen from the results of the frequency test carried out by the authorthat several causes cause students to make mistakes in writing warning dialogues, such as the number of errors in vocabulary and grammar which result in poor results which can be seen from the test results. The frequency is that there are 65.5% of students make mistakes in writing vocabulary and there are 37.9% make mistakes in writing grammar, where the results obtained are that there are many errors in writing vocabulary and grammar in writing this warning sentence. This research has significant implications for improving the quality of English language education regarding writing giving warming dialogues. This research focuses on assessing student assignment results through the assessment method carried out by Etik, 2014.